Cobi: Community-Informed Conference Scheduling - Kim, Juho; Zhang, Haoqi; André, Paul; Chilton, Lydia; Bhardwaj, Anant; Karger, David; Dow, Steven; Miller, Robert (Proceedings of the AAAI Conference on Human Computation and Crowdsourcing, 2013)
Creating a schedule for a large multi-track conference requires considering the preferences and constraints of organizers, authors, and attendees. Traditionally, a few dedicated organizers manage the size and complexity of the schedule with limited information and coverage. Cobi presents an alternative approach to conference scheduling by engaging the entire community to take active roles in the planning process. It consists of a collection of crowdsourcing applications that elicit preferences and constraints from the community, and software that enable organizers and other community members to take informed actions based on collected information.